Mixtoscutella ussowi - Grischenko, Andrei V.; Gordon, Dennis P.; Taylor, Paul D.; Kuklinski, Piotr; Denisenko, Nina V.; Spencer-Jones, Mary E.; Ostrovsky, Andrew N. (Zenodo, 2022)
Mixtoscutella ussowi (Kluge, 1908) (Figs 28, 33H) Schizoporella ussowi Kluge, 1908a, p. 527, figs 2a–c. Hippodiplosia ussowi : Kluge 1953, p. 175; 1961, p. 135; 1962, p. 501, fig. 348; 1975, p. 609, fig. 348; Androsova 1958, p. 139, fig. 62; Kluge et al . 1959, p. 212. Hippodiplosia smitti : Osburn 1933, p. 330, pl. 9, fig. 6. Hippoporina ussowi : Gontar & Denisenko 1989, p. 358; Denisenko 1990, p. 37; 2013, p. 184; Grischenko 1997, p. 189; Shunatova & Ostrovsky 2001, p. 115. Rhamphostomella ussowi : Winston & Hayward 2012, p. 124, fig. 80. Material examined. Lectotype : ZIRAS 4 /2331, single colony fragment, Stn 8, 27 June 1876, estuary of Mezen River, White Sea, dredge, collector K.S. Merezhkovsky. ZIRAS 13 /13526, colony fragment, summer 1897, Zajatskie Islands of the Solovetskiy Archipelago, Onego Bay, White Sea, dredge, collector G.A. Kluge. ZIRAS 14 /50567, colony fragment, KIENM Collection, RV Nazarovsk , Stn 394, 18 September 1988, Korfa Gulf, eastern Kamchatka Peninsula, Bering Sea, 60°07.0ʹ N, 165°57.0ʹ E, depth 48 m, rock dredge, collector A. V. Rzhavsky. Additional material. Seven specimens. IMB Collection, Commander Intertidal Expedition (1972) Stn 194/2; KIENM Collection (1992) Stns 54, 88 (see Appendix 1 for details). Measurements. ZIRAS 14/50567, Korfa Gulf, eastern Kamchatka, Bering Sea (Fig. 28A–M). ZL, 0.67–1.13 (0.91 ± 0.11). ZW, 0.37–0.70 (0.54 ± 0.07). ZD, 0.60–0.78 ( n = 2). OrL, 0.20–0.25 (0.23 ± 0.01). OrW, 0.21–0.25 (0.23 ± 0.01). OeL, 0.35–0.43 (0.39 ± 0.02) ( n = 15). OeW, 0.36–0.44 (0.39 ± 0.02) ( n = 15). Av(s)L, 0.09–0.14 (0.11 ± 0.01). P(f)N, 32–49 (42) ( n = 10). Description. Colonies encrusting, multiserial, unilaminar (Fig. 28A), roughly circular, up to 11 × 8 mm in maximal dimension, bright-yellow to beige when alive, light yellow when dry. Zooids of medium size, oblonghexagonal, oval to irregularly polygonal, arranged in quincunx, delineated by undulating fused lateral walls. Frontal shield mixed, comprising umbonuloid and lepralioid components (Fig. 28A, D, F), ...